2016
DOI: 10.3844/ajisp.2016.99.106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mast Cell Distribution in Oral Lichen Planus and Lichenoid Lesions by Immunohistochemical and Histochemical Analysis

Abstract: The histopathological assessment of Oral Lichen Planus (OLP) and oral lichenoid lesions is relatively subjective. The distinguishing criteria established by WHO effectively reproducible when all selection criteria were fulfilling but sometimes fail to provide a reliable diagnosis. The aim of the present study was to evaluate mast cell counts and their distribution among OLP and lichenoid lesions. The density and localization of mast cells was examined in 22 patients with a diagnosis of OLP (11 patients) or ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 20 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…Juneja et al had reported that there was an increase in the mast cell numbers at sites of epithelial disruption in both OLP and OLR groups with significantly higher numbers ( P < .05) in OLP than OLR.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Juneja et al had reported that there was an increase in the mast cell numbers at sites of epithelial disruption in both OLP and OLR groups with significantly higher numbers ( P < .05) in OLP than OLR.…”
Section: Resultsmentioning
confidence: 96%
“…All 12 studies had answered the 1st research question of the mast cell number in OLP patients. 5 studies had used toluidine blue‐based staining to count the number of the mast cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations